2012
DOI: 10.1186/1471-2253-12-27
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1 and t-PA/PAI-1 complex potential markers of fibrinolytic bleeding after cardiac surgery employing cardiopulmonary bypass

Abstract: BackgroundEnhanced bleeding remains a serious problem after cardiac surgery, and fibrinolysis is often involved. We speculate that lower plasma concentrations of plasminogen activator inhibitor – 1 (PAI-1) preoperatively and tissue plasminogen activator/PAI-1 (t-PA/PAI-1) complex postoperatively might predispose for enhanced fibrinolysis and increased postoperative bleeding.MethodsTotally 88 adult patients (mean age 66 ± 10 years) scheduled for cardiac surgery, were enrolled into a prospective study. Blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
2
17
0
1
Order By: Relevance
“…Previous studies indicated that higher tissue plasminogen activator (tPA) and lower activity of plasminogen activator inhibitor (PAI) were detected in older patients. And after surgery, lower plasma concentrations of PAI-1 preoperatively leads to higher plasma levels of D-dimer in association with coagulopathy [22]. However, increasing age was not related to higher postoperative hemorrhage and infarction, which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies indicated that higher tissue plasminogen activator (tPA) and lower activity of plasminogen activator inhibitor (PAI) were detected in older patients. And after surgery, lower plasma concentrations of PAI-1 preoperatively leads to higher plasma levels of D-dimer in association with coagulopathy [22]. However, increasing age was not related to higher postoperative hemorrhage and infarction, which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Additional highly sensitive tests (such as plasmin antiplasmin assays, euglobulin time) have been described in the literature to evaluate fibrinolysis. 19 Greilich et al 20 used D-dimers to evaluate the effect of epsilon aminocaproic acid (EACA) and aprotinin on fibrinolysis. They reported that, even if D-dimers were not different between EACA and aprotinin groups, the use of the two drugs was associated with a decrease in D-dimers compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 270 patients with bleeding of unknown cause, patients had higher tPA activity levels and lower levels of tPA-PAI-1 complexes and lower PAI-1 levels, indicating a possible underlying hyperfibrinolytic disorder [5]. In a cohort of patients undergoing cardiac surgery, postoperative blood loss was associated with lower preoperative levels of PAI-1 and lower postoperative tPA-PAI-1 levels [108]. On the other hand, a study evaluating fibrinolysis in patients with a mild-to-moderate bleeding tendency of unknown cause showed no differences in PAI-1 levels between patients and healthy controls.…”
Section: Fibrinolysis In Bleeding Of Unknown Causementioning
confidence: 99%